Synthesis and the crystal structure of dimeric 1-hydroxyhexane-2, 3-dione and the spectral characteristics of a model acireductone. (29th September 2016) - Trzewik, Bartosz; Chruszcz-Lipska, Katarzyna; Miłaczewska, Anna; Opalińska-Piskorz, Joanna; Karcz, Robert; Gryboś, Robert; Oszajca, Marcin; Luberda-Durnaś, Katarzyna; Łasocha, Wiesław; Fitch, Andy; Sulikowski, Bogdan; Borowski, Tomasz
Abstract : Various forms of an ARD substrate were studied by a combination of theoretical and experimental methods. Abstract : An efficient synthetic route to 1-hydroxyhexane-2, 3-dione, which is a tautomeric form of a model acireductone, is presented here. Interestingly, the compound was found to crystallise as a stable dimer, a molecule of which contains a 1, 3-dioxolane ring. The dimer structure was solved using the PXRD (powder X-ray diffraction) method and confirmed by NMR, IR, and Raman spectroscopy and DFT calculations. The title compound dissolves in water with the formation of several monomeric forms of the model acireductone as revealed by UV-Vis and NMR spectra. The extinction coefficients of the neutral and anionic forms of the monomer were also determined.